FRI0107 A comparison of two methods of assessing cardiovascular risk in rheumatoid arthritis in a secondary care setting. (23rd January 2014) - Khan, A.; Bhagat, S.; Hughes, J.; North, J.; O'Reilly, D.; Rajagopal, V.; Skingle, S.; Slack, R.
Abstract : Background: Rheumatoid arthritis (RA) is associated with increased cardiovascular disease (CVD) risk. The UK National Institute of Health and Clinical Excellence recommends an annual CVD risk review 1 . EULAR suggests the increased CVD risk can be quantified as 1.5 times the calculated risk under certain conditions 2 . Objectives: In the UK, CVD risk can be calculated by the Joint British Societies (JBS) 2 guideline 3 or the QRisk2 calculator 4 . We compared these two methods by auditing a secondary care annual RA clinic. Methods: Patients presenting between Jan and Mar 2012 diagnosed with RA but not CVD had data collected. If recent lipid profiles were unavailable these were checked with the next bloods. Risk calculations were made post-hoc. Results: 44 patients were assessed. 25 patients were found to be high risk by JBS2 and 29 by QRisk2, with the two agreeing in 68% of cases. When limited to the 29 patients not already on primary prevention (PP), overall agreement did not change (69%) but low risk agreement increased from 59% to 67%. We noted that 11/29 patients who were high risk by both measures were not already on PP (13 by JBS2, 18 by QRisk2). QRisk2 predicted high risk more often than JBS2, except when the EULAR 1.5x risk multiplier was applied, in which case QRisk2 never predicted high risk in a JBS2 low risk patient. Numerical results were not obtained because of old age in 1 Qrisk patient and 6 JBS2 patients, while 2 patients had diabetes, for whom JBS2 is not valid. Excluding these cases, the two risk scores were positively correlated (Pearson's R=0.767, P<0.0001). They agreed closely in low risk, but varied greatly at high risk, especially at the conventional 20% threshold, reflected in wide +/- 2sd limits of agreement of +24% and -22%. Conclusions: We confirmed the need for CVD risk assessment in secondary care by finding that at least 11/29 patients not already on PP had a high CVD risk. There was significant disagreement between the two methods. QRisk2 identified more patients as being at risk than JBS2, but unpredictably. QRisk2 does not factor in time since RA diagnosis as suggested by EULAR, and may overpredict in patients recently diagnosed. QRisk2 remains attractive as it is UK specific and is usable both when data is unavailable and when patients are on PP. Our aim was to incorporate CVD risk assessment in secondary care. In our practice this would be with QRisk2 in the cases of those not already on PP, while acknowledging the result obtained does not reflect EULAR guidance. An indication of the patient's risk would then be passed on to their general practitioner to initiate and monitor treatment. References: National Collaborating Centre for Chronic Conditions. Rheumatoid arthritis: national clinical guideline for management and treatment in adults. London: Royal College of Physicians, February 2009 Peters MJL et al. EULAR evidence-based recommendations for cardiovascular risk management in patients with rheumatoid arthritis and other forms of inflammatory arthritis. Ann Rheum Dis 2010;69:325-331 Wood DA et al. JBS 2: Joint British Societies' guidelines on prevention of cardiovascular disease in clinical practice. Heart 2005;91:v1-v52 Collins GS, Altman DG. An independent and external validation of QRISK2 cardiovascular disease risk score: a prospective open cohort study. BMJ 2010;13:340:c2442 Disclosure of Interest: None Declared